Coping with a dead end by relying on your own compass: A qualitative study on illness and treatment models in the context of fibromyalgia - Van Alboom, M.; Baert, F.; Bernardes, S. F.; Bracke, P.; Goubert, L. (Qualitative Health Research, 2026)
Fibromyalgia lacks a coherent illness and treatment model, which includes a set of conceptual ideas shaping individuals’ perceptions and understandings of pain, its causing and maintaining factors, and management strategies. Developing personalized illness models that can guide treatment plans and alleviate feelings of uncertainty is of crucial importance. This study investigates how individuals with fibromyalgia develop a personal illness and treatment model while navigating the current healthcare system and explore their experiences during this process. Semi-structured interviews were conducted with 15 cis women with fibromyalgia, which were analyzed using reflexive thematic analysis. The analysis produced two themes, each including two subthemes. The first theme encompassed the difficulty of developing a comprehensive illness model due to the biomedical perspective of the healthcare system; the second theme described the importance of participants (re)gaining ownership and agency over their pain management, by constructing their own illness and treatment model. Most women in this study got stuck in the biomedical healthcare web not being provided with a clear illness and treatment model. Consequently, most women gained ownership of this process by developing their personal illness and treatment model (self-empowerment). Conversely, a few women felt powerless and paralyzed. This study underscores the importance of promoting patient empowerment in chronic pain management. Agency is undervalued in the treatment of fibromyalgia and warrants more thorough examination. Increasing knowledge about agency could enhance treatment effectiveness.